Analisis Keberlanjutan Industri Penyamak Kulit Melalui Tingkat Eko-Efisiensi Dengan Struktur Modal Tanpa Bunga - Aceng Kurniawan (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2022)
The declining profitability of the tannery industry in addition to reducing the potential for business sustainability also results in poor environmental management because it is unable to pay the cost of managing the waste generated (eco-cost). If the waste flows into the soil or rivers, these materials certainly damage the soil and water ecosystems. The purpose of this study was to determine the impact of changes in capital structure on the sustainability of the tannery industry. To find out the affordability and sustainability of an industry, the Eco Efficiency Index (EEI) can be calculated. An increase in the number of loans with an interest system will increase the cost of goods sold (HPP) and will reduce the net value of the leather tannery industry. The lower the net value, the smaller the eco-efficiency index (EEI) will be. The impact resulting from the leather tanning process using chrome on the leather tanning industry in Sukanggang Garut is Rp. 12,995,494, - for every 1,000 kg of raw leather equivalent to Rp. 12,995, - per kg of rawhide or Rp. 5,907, - per leather raw material. raw. An increase in the number of loans with an interest system will increase the cost of goods sold (HPP) and will reduce the net value of the leather tannery industry. The lower the net value, the smaller the eco-efficiency index (EEI) will be.